Development of Integrated Language Skills Assessment Instruments for Korean as a Foreign Language Learning in Higher Education - Nuraziza Aliah; Nurasia Natsir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the development of integrated language skills assessment instruments for Korean as a foreign language (KFL) learners in higher education, addressing the need for tools that reflect real-world communicative demands. Grounded in theoretical frameworks such as Bachman and Palmer's Communicative Language Ability model[1] and Vygotsky's Sociocultural Theory[2], the research employed a mixed-methods approach, including needs analysis[6], corpus studies, and pilot testing. The research process involved three primary phases: First, a comprehensive needs analysis was conducted among KFL instructors and students to identify assessment gaps and priorities. Second, authentic Korean language materials were collected to create a corpus that informed the development of contextualized assessment tasks. Finally, the instruments underwent rigorous pilot testing with 127 KFL students across three Indonesian universities.The developed assessment instruments integrate reading, writing, listening, and speaking skills through task-based scenarios that mirror authentic Korean language use contexts. These include collaborative problem-solving activities, multimedia-based comprehension tasks, and culturally situated role-plays. Statistical analysis demonstrated high inter-rater reliability (r=0.87) and construct validity when compared with established Korean proficiency measures.Results demonstrated the instruments' reliability, validity, and cultural relevance, fostering holistic skill development and promoting positive washback on teaching and learning practices. Implementation of these instruments led to significant improvements in students' integrated language performance and motivation. The study contributes to the field of Korean language assessment by providing empirically validated tools that bridge classroom learning with real-world language application in higher education contexts.